Video Profile As a Promotional Media in The Semesta Store Malang City - Jeremiah, Sean Elbert; Wardana, Ditya; Wardani, Lely Surya (Jurnal Pengabdian Masyarakat, 2024)
Purpose: Profile videos as promotional media can be utilized across multiple platforms, including social media, websites, portfolios, YouTube, presentations, marketing initiatives, events, and webinars. This promotional material is crucial for enhancing sales and motivating people to make purchases. When utilized effectively, promotional media can enhance a company's exposure and appeal, positively influencing sales. Method: The process consists of three stages: pre-production, which involves conducting a SWOT analysis, brainstorming concepts, and creating storyboards. The production step involves video editing, followed by the post-production stage, which entails releasing the video on social media. Practical Applications: The anticipated outcomes of producing a profile video include a substantial enhancement in brand awareness, the engagement of the target audience, and the cultivation of stronger customer relationships through the effective communication of the company's vision, mission, and values, thereby fostering conversions and increased loyalty in the future. Conclusion: This profile video functions to promote the shop through publications on social media such as websites, Facebook, Instagram and YouTube. Choosing a strategy for using profile videos can function as promotional media on various online platforms in the current digital era, in order to increase company visibility and have a positive impact on company sales and revenues.